Minimal Important Difference (MID) of two commonly used outcome measures for foot problems - Radford Joel A; Landorf Karl B; Hudson Susie (Journal of Foot and Ankle Research, 2010)
Abstract Background The Visual Analogue Scale (VAS) and the Foot Health Status Questionnaire (FHSQ) are two commonly used outcome measures for evaluating foot health. This study aimed to calculate the Minimal Important Difference (MID) of the VAS and the FHSQ. Methods 184 participants with plantar heel pain were recruited from the general public to take part in two randomised trials (92 participants in each trial) that studied the effectiveness of two conservative interventions for plantar heel pain. Data from these participants were used to calculate the MIDs of the VAS and the FHSQ. An anchor-based method was used to calculate the MIDs. Two distinct types of pain were investigated for the VAS: average pain and first-step pain. All four domains of the FHSQ were investigated: foot pain, foot function, footwear and general foot health. Results The MID for the VAS using the anchor-based approach was -8 mm (95% CI: -12 to -4) for average pain and -19 mm (95% CI: -25 to -13) for first-step pain on the 100 mm VAS. The MID for the FHSQ was 13 points (95% CI: 6 to 19) for pain and 7 points (95% CI: 1 to 13) for function. The MID for the footwear domain of the FHSQ was -2 points (95% CI: -8 to 4) and 0 points (95% CI: -7 to 6) for the general foot health domain of the FHSQ. Conclusion The results of this study provide additional evidence for MID values of the VAS and the FHSQ for plantar heel pain. This is important for clinicians and researchers as it provides a greater understanding of how much improvement is required by a patient before a minimal, worthwhile change is experienced. The calculated MIDs will also assist researchers with prospective sample size calculations.